2013
DOI: 10.5539/ijbm.v8n5p89
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Reorder Point Strategy of Assembly Manufacturer with Random Variables

Abstract: For assembly system, randomness and variableness make it impossible to control the inventory accurately specially. Because the negative effect of them have ripple effects. So we investigate reorder point optimization strategy of assembly manufacturing system with random demand and random lead time. We seek the manufacturers order strategy for the minimum integration of the supply chain inventory cost. And we use scale benefits parameters of suppliers in this system to reflect actual influence of the lot's scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies have found a formula that can help in determining inventory models that can form the basis of determining inventory policies. Li et.al (2013) [8] conducted a reorder point optimization research on manufacturing spare parts systems under permit conditions and random leadtime. With demand assumed to be normally distributed.…”
Section: Fig 2 Inventory Level and Cost Relationmentioning
confidence: 99%
“…Several previous studies have found a formula that can help in determining inventory models that can form the basis of determining inventory policies. Li et.al (2013) [8] conducted a reorder point optimization research on manufacturing spare parts systems under permit conditions and random leadtime. With demand assumed to be normally distributed.…”
Section: Fig 2 Inventory Level and Cost Relationmentioning
confidence: 99%